The pro-inflammatory signalling regulator Stat4 promotes vasculogenesis of great vessels derived from endothelial precursors - Meng, Zhao-Zheng (Nat Commun, 2017)
Vasculogenic defects of great vessels (GVs) are a major cause of congenital cardiovascular diseases. However, genetic regulators of endothelial precursors in GV vasculogenesis remain largely unknown. Here we show that Stat4, a transcription factor known for its regulatory role of pro-inflammatory signalling, promotes GV vasculogenesis in zebrafish. We find stat4 transcripts highly enriched in nkx2.5(+) endothelial precursors in the pharynx and demonstrate that genetic ablation of stat4 causes stenosis of pharyngeal arch arteries (PAAs) by suppressing PAAs 3–6 angioblast development. We further show that stat4 is a downstream target of nkx2.5 and that it autonomously promotes proliferation of endothelial precursors of the mesoderm. Mechanistically, stat4 regulates the emerging PAA angioblasts by inhibiting the expression of hdac3 and counteracting the effect of stat1a. Altogether, our study establishes a role for Stat4 in zebrafish great vessel development, and suggests that Stat4 may serve as a therapeutic target for GV defects.